Metaphors of Depression in Rupi Kaur's Poetry Collection Home Body - Lehtinen, Jenna (My University, 2025)
Depression is a mental illness that has been plagued by stigma and indescribability throughout its history. The frustrating task of describing depression outright has driven many of those who suffer from it to try and express their feelings and thoughts through art. The difficulty of pairing any words with depression makes literature the most fascinating form of this artistic expression. That is why in this thesis I look into how depression is handled in poetry. After establishing the relationship that depression and language have, I examine the relationship between depression and poetry. With these findings, I am able to analyse Rupi Kaur’s poetry in her poetry collection Home Body (2020) and how the metaphors associated with depression show up in her works. The most common way to describe depression in literature is through metaphors. I show how these metaphors came to be, why they seem overused, and yet remain the most popular way to describe symptoms of depression. These metaphors revolve around darkness, slowness and disassociation. I also bring up how, in some cases where the illness is not lifelong, the illness can be a rebirth, a way to find hope and happiness through changing thought processes. My findings show that Rupi Kaur uses several of the metaphors linked to depression in her works in Home Body. The metaphors of darkness, emptiness and worthlessness are prominent in the collection and metaphors of hopefulness become prominent near the end of the collection.
Keywords: depression, poetry, depression in literature, Rupi Kaur, metaphors